EKSISTENSI DAN PERUBAHAN NILAI GOTONG ROYONG DALAM KEHIDUPAN BERMASYARAKAT DI DESA WATUPRAPAT - Sakdiya, Khalimatus; Ayu Maya Damayanti; Innayatul Laili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the continued existence of gotong royong (mutual cooperation) and identify changes in the values ​​associated with it within the community of Watuprapat Village, Nguling District, Pasuruan Regency. A qualitative method employing a case study approach was used. Data were collected through in-depth interviews, direct observation, and document analysis. The research reveals that the value of gotong royong persists and is applied in the community's daily life, though its forms and meanings have evolved compared to the past. This shift is evident in the way it is practiced: while it was once voluntary, unpaid, and all-encompassing, it has now become more practical and structured, often involving payment or cost reimbursement. Factors driving these changes include economic growth, shifts in social structure, the impact of education, and advancements in information technology. Despite these changes, the value of gotong royong continues to strengthen interpersonal relationships and maintain a sense of togetherness within the village community.